Nationalism Over Globalization amidst COVID-19 Pandemic and Its Impact on Indonesia’s Food Security - Prawita Meidi Handayani (Jurnal Politica, 2020)
COVID-19 has posed new challenges to globalization. It further perpetuates the rising trend of nationalism that has been ongoing for quite some time. At the start of the pandemic, one will automatically point the finger to cross-border travelers and people who can perform a high transnational movement. This phenomenon further increases the rapid spread of the virus on a global scale and disrupts the global supply chain that comes with it. When the outbreak first emerged, most policymakers wrongly assumed that the COVID-19 pandemic would only have a brief, limited, China-specific impact. As a matter of fact, the pandemic is generating a global shock and economic slowdown, risking to turn for the worse into recession. This pandemic has strongly highlighted the many downsides of extensive international integration and thus provoked fears of foreigners. It later gave legitimacy to national restrictions on global trade and movement of people. As it turned out, COVID-19 is the catalyst needed to further enhance the rise of nationalism. This phenomenon will, eventually, have negative repercussions on Indonesia’s food security.AbstrakCOVID-19 telah membawa tantangan baru bagi globalisasi. Tren nasionalisme yang memang telah berkembang di seluruh dunia kemudian diperburuk oleh pandemi COVID-19. Saat dimulainya pandemi, secara otomatis seseorang akan menyalahkan para pelancong lintas batas dan orang-orang yang memiliki kemampuan untuk melakukan pergerakan transnasional yang tinggi. Fenomena ini yang kemudian semakin meningkatkan penyebaran virus yang cepat dalam skala global dan gangguan pada rantai pasokan global. Pada awal merebaknya wabah COVID-19, sebagian besar penyusun kebijakan salah berasumsi bahwa pandemi ini hanya akan memiliki dampak singkat dan terbatas hanya terhadap Cina. Pada kenyataannya, pandemi ini telah mengakibatkan guncangan global dan perlambatan ekonomi yang berpotensi menjadi resesi global. Pandemi ini sangat menyoroti banyak kerugian dari integrasi internasional yang luas dan memicu ketakutan terhadap orang asing. Hal ini kemudian memberikan legitimasi pada pembatasan nasional terhadap perdagangan global dan pergerakan manusia. COVID-19 telah menjadi katalis yang dibutuhkan untuk lebih meningkatkan kebangkitan nasionalisme. Fenomena ini pada akhirnya akan berdampak negatif terhadap ketahanan pangan Indonesia.